DESENVOLVIMENTO DO CAPIM-CONVERT HD364® COM ADUBAÇÃO LÍQUIDA - SAGISAKA, Karina Hayumi Silva; PAIVA, Luísa Melville; BREVILIERI, Redney Gomes; FLEITAS, Alex Coene; OLIVEIRA, Carlos Magno de Paula (ANAIS DO ENIC, 2017)
-